The Effect of Labour Cost Reduction on Employment of Vulnerable Groups: Evaluation of the Hungarian Job Protection Act - Svraka, András (Public Finance Quarterly, 2023)
In 2013 Hungary introduced large scale targeted employers’ social security contribution cuts for the young, old, lowskilled, and other marginally attached workforce, called the Job Protection Act. In this paper I estimate the employment effects of the programme for the main target groups using the discontinuities in the JPA’s design in a differences in differences framework on administrative datasources. My estimates show robust and economically significant employment effects for the Job Protection Act, a total 1.2 point increase in employment rate three years after the introduction. The Job Protection Act was highly effective in the young and low-skilled target groups, with high self-financing ratios, while it was only marginally effective in the old target group. The results suggests that targeted tax incentives can be a cost-efficient way of increasing employment in vulnerable groups.